Rising household debt in Malaysia: macroeconomics determinant / Alyaa Amanina Azhar - Azhar, Alyaa Amanina Azhar (Faculty of Business Management, 2017)
Household debt of Malaysia keep growing year by year. This situation can give big impact to the economic system if the debt reach at one point of level that can’t be controlled. High in household debt is not only affected to the economy, but also affected on the financial stability. The main reason why households is taking on loan is to fulfil their expenditure and dependence on future income, the attitude and behaviour of the individual himself, low in the cost of borrowing that give opportunity to household to borrow, easy to get credit facilities which boosts spending on credit, increase in cost of living and increase in housing price, and continued economic growth. All this reasons made household feel comfortable in taking on loan. The objective of this study is to find the factors that affect the household debt in Malaysia. The variables selected is from macroeconomic variables. The data are taken from the year 1985 to 2015. Multiple Regression test are used in this study resulting consumer price index and lending interest rate are significant with household debt.